Tingkat Kecemasan Mahasiswa UKM Basket Sebelum Pertandingan : Studi Kasus pada Mahasiswa PKO Universitas Negeri Surabaya Angkatan 2023 - Muhammad Zaidan Barki Muslim; Ilo Raditio Wiriawan; Anung Priambodo; Achmad Widodo (STIKes Ibnu Sina Ajibarang, 2025)
Anxiety is an important factor that affects athlete performance before a match. This study aims to measure the level of anxiety of students of Basketball UKM Universitas Negeri Surabaya (Unesa) before the match, and to explore the factors that influence it. The research method used is descriptive quantitative with a survey approach to 12 Basketball UKM students. Data were collected through the Sport Anxiety Scale questionnaire which includes somatic, cognitive, motoric, and affective aspects. The results showed that most students had low levels of anxiety (75%), with somatic and affective anxiety more dominant in the low to very low categories. These findings highlight the need for anxiety management strategies, such as relaxation training and mental strengthening, to improve athlete performance and well-being. This study provides practical implications in the development of anxiety management programs for student athletes.